Finnegans wake eaudiobook - Joyce, James (Naxos AudioBooks, 2021)
'Riverrun past Eve and Adam's, from swerve of shore to bend of bay, brings us by a commodius vicus of recirculation back to Howth Castle and Environs...' So starts Finnegans Wake , the greatest challenge in 20th-century literature. Who is Humphrey Chimpden Earwicker? And what did he get up to in Phoenix Park? And what did Anna Livia Plurabelle have to say about it? In the rich nighttime and the language of dreams, here are history, anecdote, myth, folk tale and, above all, a wondrous sense of humour, coloured by a clear sense of humanity. In this exceptional reading by the Irish actor Barry McGovern, with Marcella Riordan, the world of the Wake is more accessible than ever before.